Peer group and friend influences on the social acceptability of adolescent book reading - Merga, Margaret (2014)
Increasing recreational reading is a priority in a climate of growing adolescent aliteracy. Raising the social appeal of books has been identified as one potential avenue for arresting this trend. An understanding of the current social acceptability of book reading amongst contemporary adolescents is important in informing an effective approach to raise the status of book reading, as is insight into how this status impacts upon attitudes toward, and engagement in, recreational book reading. Friend and peer group attitudes may impact upon the palatability of recreational book reading, and this impact may differ for gender. Findings from the 2012 West Australian Study in Adolescent Book Reading (WASABR) are analyzed to provide insight into these key areas, with implications for educators considered. FREE author podcast © 2014 International Reading Association.